Love Ancient Perspectives - Grødum, Kari; Hägg, Henny Fiskå; Kaufman, John; Tollefsen, Torstein Theodor (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"This anthology presents and discusses perceptions on the notion of love in ancient philosophy and early Christian theology. The notion of love is discussed firstly in two critical readings of Anders Nygren's study Agape and Eros (1930-36). Nygren´s distinction of eros, on the one hand, as an egocentric, human love and agape, on the other hand, as Christian, theocentric and divine love, has long been received almost as a dogmatic truth and prevented a more nuanced understanding. The metaphysics and ethics of love are further discussed in relation to Platonic, Neoplatonic, biblical and early Christian - especially Eastern Christian - thinking. Related questions such as "Is all love essentially divine?"and "Is unselfish love possible?" and themes such as love as a unifying force, and ascetical love, are also discussed. The papers were first presented at an international research seminar, The Metochi Seminar, at the University of Agder´s study centre in Greece (the Metochi Study Centre), on the island of Lesvos."